Iptycenes chemistry : from synthesis to applications - Chen, Chuan-Feng; Ma, Ying-Xian (Heidelberg, 2013)
"Provides a comprehensive overview of the development of iptycene chemistry in the past seventy years. This book covers: (1) the basic nomenclature and general properties of iptycenes and their derivatives; (2) the synthesis and functionalization reactions of triptycenes, pentiptycenes, higher iptycenes, heterotriptycenes, and homotriptycenes; (3) the methods for the preparation of iptycene-based polymers with different types; and (4) the applications of iptycenes and their derivatives in molecular machines, materials science, host-guest chemistry, self-assembly, coordination chemistry, physical organic chemistry, medicinal chemistry, and so on. Consequently, such a book is not only helpful to researchers working in iptycene chemistry, but can also facilitate future research in wide areas."--Publisher description.
Incluye referencias bibliográficas
Keywords: COMPUESTOS AROMATICOS; POLIMEROS